1994
DOI: 10.1002/qua.560520213
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativity and electron correlation effects on hydrogen bonding in infinite systems

Abstract: Structural and electronic properties of hydrogen-bonded infinite chains of hydrogen cyanide and formamide molecules have been investigated by the ab initio crystal orbital method using several, partly highly polarized, atomic basis sets of increasing size at the Hartree-Fock (HF) level and by including electron correlation effects in the second order of Mller-Plesset perturbation theory. The results obtained show that hydrogen bonding in molecular crystals of the type investigated is a highly cooperative pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 65 publications
2
13
0
Order By: Relevance
“…In hydrogen-bonded clusters, cooperativity is usually estimated from the lengthening in the X−H bonds involved in hydrogen bonding interactions. In our case, N−H bond distances increased by up to 0.006 Å with the correlated methods; this value is similar to that obtained for the N−N bond and also to reported data for other hydrogen-bonded systems. , Polar molecules frequently exhibit an increased dipole moment relative to the vector addition of the dipole moments for the monomers. The electric field created by each molecule induces a dipole moment in its neighbor that can modify the net dipole moment of the cluster. , Table compares the dipole moment for the cluster with the result of the vector addition of the values obtained for the individual molecules.…”
Section: Resultssupporting
confidence: 91%
“…In hydrogen-bonded clusters, cooperativity is usually estimated from the lengthening in the X−H bonds involved in hydrogen bonding interactions. In our case, N−H bond distances increased by up to 0.006 Å with the correlated methods; this value is similar to that obtained for the N−N bond and also to reported data for other hydrogen-bonded systems. , Polar molecules frequently exhibit an increased dipole moment relative to the vector addition of the dipole moments for the monomers. The electric field created by each molecule induces a dipole moment in its neighbor that can modify the net dipole moment of the cluster. , Table compares the dipole moment for the cluster with the result of the vector addition of the values obtained for the individual molecules.…”
Section: Resultssupporting
confidence: 91%
“…However, the pattern of hydrogen bonding varies considerably. Previous research 12,[26][27][28][29][30] has shown that the strength of infinite chain hydrogen bonds is not the sum of the corresponding isolated intermolecular interactions, rather, the total energy of these hydrogen bond configurations will be lower due to cooperative effects. In hydrogen patterns such as … O-H … O-H … O-H … the cooperative effect is referred to as s-cooperativity.…”
Section: Relationship Between Melting Point and Structural Featuresmentioning
confidence: 96%
“…This has prompted several studies on cooperativity involving weak Hbonds, a few of them dealing with negative cooperativity as well 38,39,40,41,42,43,44 . Nevertheless, most of these studies, that include both experimental 45,17,46,47,48 and theoretical 49,50,51,52,53 works, have dealt with how a weak H-bond cooperatively stabilizes (or destabilizes) a classical H-bond in either inter-or intra molecular fashion. On the other hand, not too many studies are available in existing literature on how weak H-bonds cooperatively stabilize themselves in molecular clusters, investigations on C-H-N interactions in HCN 54 and cyanoacetylene 55 clusters and C-H-π in ethyne clusters 56 and S-H-S H-bond in H 2 S clusters 57 being a few of them.…”
Section: Introductionmentioning
confidence: 99%